An improved design to capture magnetic microparticles for capillary electrophoresis based immobilized microenzyme reactors. Issue 7 (19th January 2018) - Ramana, Pranov; Schejbal, Jan; Houthoofd, Kristof; Martens, Johan; Adams, Erwin; Augustijns, Patrick; Glatz, Zdenĕk; Van Schepdael, Ann
Abstract: In this paper, we demonstrate the effectiveness of a new 3D printed magnet holder that enables capture of magnetic microparticles in commercially available capillary electrophoresis equipment with a liquid or air based coolant system. The design as well as the method to capture magnetic microparticles inside the capillary are discussed. This setup was tested at temperature and pH values suitable for performing enzymatic reactions. To demonstrate its applicability in CE‐ immobilized microenzyme reactors (IMER) development, human flavin‐containing monooxygenase 3 and bovine serum albumin were immobilized on amino functionalized magnetic microparticles using glutaraldehyde. These microparticles were subsequently used to perform in‐line capillary electrophoresis with clozapine as a model substrate. This setup could be used further to establish CE‐IMERs of other drug metabolic enzymes in a commercially available liquid based capillary coolant system. The CE‐IMER setup was successful, although a subsequent decrease in enzyme activity was observed on repeated runs.